For Better or Worse? The Effects of Physical Education on Child Development - Michael C. Knaus; Michael Lechner; Anne K. Reimers (Institute of Labor Economics (IZA), 2018)
This study analyses the effects of regular physical education at school on cognitive skills, non-cognitive skills, motor skills, physical activity, and health. It is based on a very informative data set, the German Motorik-Modul, and identifies the effect by using variation in the required numbers of physical education lessons across and within German federal states. The results show improvements in cognitive skills. Boys' non-cognitive skills are adversely affected driven by increased peer relation problems. For girls, the results suggest improvements in motor skills and increased extra-curricular physical activities. Generally, we find no statistically significant effects on health parameters.
Keywords: I26; Z28; I12; 330; physical education; cognitive skills; non-cognitive skills; motor skills; physical activity; health